International Genome-Wide Association Study Consortium Identifies Novel Loci Associated With Blood Pressure in Children and Adolescents. (June 2016) - Parmar, Priyakumari Ganesh; Taal, H. Rob; Timpson, Nicholas J.; Thiering, Elisabeth; Lehtimäki, Terho; Marinelli, Marcella; Lind, Penelope A.; Howe, Laura D.; Verwoert, Germaine; Aalto, Ville; Uitterlinden, Andre G.; Briollais, Laurent; et al.
Abstract : Background—: Our aim was to identify genetic variants associated with blood pressure (BP) in childhood and adolescence. Methods and Results—: Genome-wide association study data from participating European ancestry cohorts of the Early Genetics and Lifecourse Epidemiology (EAGLE) Consortium was meta-analyzed across 3 epochs; prepuberty (4–7 years), puberty (8–12 years), and postpuberty (13–20 years). Two novel loci were identified as having genome-wide associations with systolic BP across specific age epochs: rs1563894 ( ITGA11, located in active H3K27Ac mark and transcription factor chromatin immunoprecipitation and 5′-C-phosphate-G-3′ methylation site) during prepuberty ( P =2.86×10 –8 ) and rs872256 during puberty ( P =8.67×10 –9 ). Several single-nucleotide polymorphism clusters were also associated with childhood BP at P <5×10 –3 . Using a P value threshold of <5×10 –3, we found some overlap in variants across the different age epochs within our study and between several single-nucleotide polymorphisms in any of the 3 epochs and adult BP-related single-nucleotide polymorphisms. Conclusions—: Our results suggest that genetic determinants of BP act from childhood, develop over the lifecourse, and show some evidence of age-specific effects. Abstract : Supplemental Digital Content is available in the text.